Impact of treatment for bacterial vaginosis on prematurity among Brazilian pregnant women: a retrospective cohort study - Camargo, Rodrigo Pauperio Soares de; Simões, José Antonio; Cecatti, José Guilherme; Alves, Valéria Moraes Nader; Faro, Sebastian (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Bacterial vaginosis has been associated with prematurity and other perinatal complications. However, the efﬁcacy of the treatment for preventing such complications has not yet been well established. The objective of this study was to evaluate the impact of treatment for bacterial vaginosis on a low-risk population of Brazilian pregnant women, in order to prevent prematurity and other perinatal complications. DESIGN AND SETTING: Observational retrospec- tive cohort study, at the Obstetric and Gynecology Department, Universidade Estadual de Campinas (Unicamp). METHODS: Vaginal bacterioscopy results from 785 low-risk pregnant women were studied. Three different groups of women were identiﬁed: 580 without bacterial vaginosis during pregnancy, 134 with bacterial vaginosis treated using imidazoles (metronidazole, tinidazole, or secnidazole) during pregnancy, and 71 with bacterial vaginosis not treated during pregnancy. The diagnosis of bacterial vaginosis was based on Nugent’s criteria, from the vaginal bacterioscopy performed during the ﬁrst prenatal care visit. RESULTS: The frequency of prematurity was 5.5% among the women without bacterial vaginosis, 22.5% among those with untreated bacterial vaginosis and 3.7% among those with treated bacterial vaginosis. The risk ratios for perinatal complications were signiﬁcantly higher in the group with untreated bacterial vaginosis: premature rupture of membranes, 7.5 (95% CI: 1.9-34.9); preterm labor, 3.4 (95% CI: 1.4-8.1); preterm birth, 6.0 (95% CI: 1.9-19.7); and low birth weight, 4.2 (95% CI: 1.2-14.3). CONCLUSION: The treatment of bacterial vagino- sis signiﬁcantly reduced the rates of prematurity and other perinatal complications among these low-risk Brazilian pregnant women, regardless of the history of previous preterm delivery.